2008
DOI: 10.1007/s00467-008-0884-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium overload on renal function of offspring from diabetic mothers

Abstract: The aim if this study was to evaluate the effect of sodium overload on blood pressure and renal function in the offspring of diabetic rat mothers. Diabetes was induced with a single dose of streptozotocin before mating. Experimental groups were control (C), offspring from diabetic mother (D), control with sodium chloride (NaCl) overload (CS), and offspring from diabetic mother submitted to NaCl overload (DS). After weaning, all groups received food ad libitum; groups C and D had water ad libitum, and CS and DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…No significant differences in blood pressure, heart rate, body weight, and Lee index were observed between the offspring of diabetic dams and controls, suggesting normal development of the evaluated cases, in agreement with previous data (1,12).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…No significant differences in blood pressure, heart rate, body weight, and Lee index were observed between the offspring of diabetic dams and controls, suggesting normal development of the evaluated cases, in agreement with previous data (1,12).…”
Section: Discussionsupporting
confidence: 81%
“…These events may lead to modifications in the metabolism and mechanisms of growth of the offspring, resulting in an increase of susceptibility to chronic disease in later life (10). Several studies have shown an association between diseases of adulthood, such as diabetes and hypertension, and changes during pregnancy, particularly in the kidney (1,3,11,12). However, no studies have correlated the influence of intrauterine environment changes on the development of new lesions acquired during adulthood, such as AKI.…”
mentioning
confidence: 99%
“…In kidney disease, renal influx/production of L-arginine can be lower than normal, resulting in locally reduced production of NO. This could be valid in DO because an important decline in glomerular filtration rate was observed in several studies (8)(9)(10)23). Moreover, decreased renal ANG 1-7 content could also interfere with NO production, as suggested by Li et al (41).…”
Section: Nitric Oxide Systemmentioning
confidence: 84%
“…In others studies, Rocha et al (8) and Magaton et al (9) examined the effect of diabetes mellitus induced in rats before mating, on the blood pressure and renal function of the adult offspring and observed development of hypertension without a reduction in nephron numbers. In the studies by our group (8)(9)(10)23), diabetes induction took place before pregnancy, preventing the effect of STZ on the development of the fetus. Moreover, in the studies by Amri et al (22), the nephron count was performed using glomerular isolation.…”
Section: Maternal Diabetes Mellitusmentioning
confidence: 99%
“…A previous article from the same group demonstrated a role of the NF-kappaB pathway in impaired nephrogenesis of the offspring of diabetic rats [61]. These results demonstrate that the effect of maternal diabetes can, at least in the animal model, be enhanced by simultaneous sodium chloride overload [62].…”
Section: Imediate Effectsmentioning
confidence: 85%